Ectoparasites from the South American sea lion (Otaria flavescens) from Peruvian coast - Gomez-Puerta, Luis A. (2015)
Two species of ectoparasites were collected from a South American sea lion (Otaria flavescens) found stranded on the beaches of Chorrillos in Lima, Peru. The ectoparasites were identified as Antarctophthirus microchir (Phthiraptera) and Orthohalarachne attenuata (Acari). Some morphological characteristics are described in this report. The finding of these ectoparasites is the first records in Peru.